A Scoping Review Approach: Analysis Of The Development And Challenges Of Tax Compliance In The Digital Era - Nurul Izzah Lubis; Umi Khairiah (ACCUMULATED JOURNAL, 2026)
The rapid development of digital technology has transformed tax administration systems worldwide by improving efficiency, transparency, and compliance monitoring, while also creating new challenges related to the digital economy such as cross-border transactions and platform-based business models. This study aims to analyze the development, determinants, challenges, and research gaps of digital tax compliance using a qualitative descriptive approach with a scoping review method, based on literature from international journals and institutional reports published between 2020 and 2025. The findings indicate that digital tax compliance is influenced by three main factors: behavioral factors (tax morale and trust), technological factors (system usability and digital infrastructure), and institutional factors (governance and regulatory frameworks). In addition, several challenges are identified, including the digital divide, system complexity, data privacy concerns, and institutional limitations, particularly in developing countries. The study also finds that existing literature remains fragmented and lacks an integrated framework. Therefore, this study proposes the Integrated Digital Tax Compliance Model (IDTCM) as a comprehensive framework to better understand tax compliance in the digital era and to provide insights for policymakers and future research.